Secukinumab for the treatment of psoriasis, psoriatic arthritis, and axial spondyloarthritis: Physical and pharmacological properties underlie the observed clinical efficacy and safety - Kolbinger, Frank; Di Padova, Franco; Deodhar, Atul; Hawkes, Jason E.; Huppertz, Christine; Kuiper, Torsten; McInnes, Iain B.; Ritchlin, Christopher T.; Rosmarin, David; Schett, Georg; Carballido, José M.; Häusermann, Peter; et al. (Pharmacology & Therapeutics, 2021)
Psoriasis, psoriatic arthritis, and axial spondyloarthritis are systemic inflammatory diseases, each commonly manifesting as a spectrum of symptoms, complications, and comorbidities that arise differently in individual patients. Drugs targeting inflammatory cytokines common to the pathogenesis of each of these conditions have been developed, although their specific actions in the different tissues involved are variable. For a drug to be effective, it must be efficiently delivered to and locally bioactive in disease-relevant tissues. Detailed clinical data shed light on the therapeutic effects of individual biologics on specific domains or clinical manifestations of disease and assist in guiding treatment decisions. Pharmacologic, molecular, and functional properties of drugs strongly impact their observed safety and efficacy, and an understanding of these properties provides complementary insight. Secukinumab, a fully human monoclonal IgG1/κ antibody selectively targeting interleukin (IL)-17A, has been in clinical use for >6 years in the treatment of moderate to severe psoriasis, psoriatic arthritis, and both radiographic (also known as ankylosing spondylitis) and nonradiographic axial spondyloarthritis. In this review, we discuss pharmacokinetic and pharmacodynamic data for secukinumab to introduce clinicians to the pharmacological properties of this widely used drug. Understanding how these properties affect the observed clinical efficacy, safety, and tolerability of this drug in the treatment of IL-17A–mediated systemic inflammatory diseases is important for all physicians treating these conditions.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Axial spondyloarthritis; Biologics; IL-17; Psoriasis; Psoriatic arthritis; Secukinumab